Influence of human resource development skills towards work performance of agriculture extension agent - Arif Shah, Jasmin; Mohamed Haris, Nur Bahiah; Abd Rahman, Muhammad Faiq Hafiz (HH Publisher, 2020)
Agriculture extension primarily deals with the human resource development (HRD) skills as well as knowledge. In the agriculture scope, all extension agents must have the knowledge, training, and skills to fulfil the requirement as a good agricultural extension agent. As the profession of extension agents continues to grow, it is important to know the human resource development (HRD) skills gained by the extension agent of agriculture to measure their performance in the extension job. Thus, this study determines the influence of human resource development (HRD) skills factor with work performance among agriculture extension agent. This is descriptive and correlational research design. Using a quantitative survey methodology consists of 5 sections of questions (A, B, C, D and E). 182 respondents were participated in this study as a sample. Simple random sampling technique has been used to choose the sample. Data has been gathered from the respondents using a self-administered questionnaire. Data has been analysed using IBM SPSS version 25 to indicate the descriptive and inferential methods. In results, the level of HRD skills and performance of agricultural extension agent is moderate. All HRD skills show a positive and high correlation with agriculture extension agent work performance. The highest factor contributing to work performance is social skills followed by decision-making skills. The two factors from HRD skills (social and decision making) accounted for 72% significantly to the performance of the agriculture extension agent job. The main purpose of this study is to provide beneficial information’s for the extension agents, respondents and organizational framework in term of relationship between the work performance towards the agriculture sector in Malaysia. This study provides insights into the theory and practice of agriculture extension agents in Malaysia.